Identification of a common cyanobacterial symbiont associated with Azolla spp. through molecular and morphological characterization of free-living and symbiotic cyanobacteria. - Gebhardt, J S (1991)
Symbiotically associated cyanobacteria from Azolla mexicana and Azolla pinnata were isolated and cultured in a free-living state. Morphological analyses revealed differences between the free-living isolates and their symbiotic counterparts, as did restriction fragment length polymorphism (RFLP) analyses with both single-copy glnA and rbcS gene probes and a multicopy psbA gene probe. RFLP analyses with Anabaena sp. strain PCC 7120 nifD excision element probes, including an xisA gene probe, detected homologous sequences in DNA extracted from the free-living isolates. Sequences homologous to these probes were not detected in DNA from the symbiotically associated cyanobacteria. These analyses indicated that the isolates were not identical to the major cyanobacterial symbiont species residing in leaf cavities of Azolla spp. Nevertheless, striking similarities between several free-living isolates were observed. In every instance, the isolate from A. pinnata displayed banding patterns virtually identical to those of free-living cultures previously isolated from Azolla caroliniana and Azolla filiculoides. These results suggest the ubiquitous presence of a culturable minor cyanobacterial symbiont in at least three species of Azolla.